Managing Financing Risk In Islamic Banks Across Asean: The Role Of Financial Performance And Macroeconomic Factors - Iqbal, Muhammad; Darmawan, Arif; Syafril, Syafwendi (At-tijaroh: Jurnal Ilmu Manajemen dan Bisnis Islam, 2024)
This study rigorously examines the influence of Financial Performance and Macroeconomic Factors on the financing risk associated with Islamic banks within the ASEAN region. The analysis utilizes panel data collected from five countries—Indonesia, Malaysia, Brunei Darussalam, Thailand, and the Philippines—spanning the period from 2010 to 2019. A dynamic panel regression methodology, specifically the Arellano-Bond Generalized Method of Moments (GMM), is employed for this purpose. The findings indicate that Liquidity Risk (LRISK), Profitability (ROE), and Good Governance (GGV) significantly exacerbate financing risk, whereas the Capital Ratio (CAR) is found to significantly mitigate it. Conversely, Economic Growth (GDP) does not demonstrate a significant effect. Furthermore, financing risk is affected by its value in the preceding period (RISKt-1), underscoring its dynamic nature. These results highlight the crucial role of effective internal bank management in alleviating financing risks through enhanced capital adequacy, judicious liquidity management, and the implementation of sound governance practices. This study endeavors to contribute to the advancement of risk management strategies for Islamic banks in the ASEAN region.